Analysis of text books for learning Islamic education based on digital media in Indonesia - Nurochim Nurochim (Jurnal Konseling dan Pendidikan, 2022)
This research aimed to find a "sense of power" in the texts as a discourse. The discourse chosen in this study was the Islamic Religious Education book which is used as a textbook. The Islamic Religious Education textbooks were selected from elementary school, junior high school, and senior high school levels. The theory used as the basis for analysis of this text was the theory of critical discourse analysis (CDA) from Fairclough. The theory suggests that the text is discursive and social practices. The research method used was literature research method, because it used ready-to-use texts, as secondary data. This study was a qualitative study because it used non-numerical data collection procedures with descriptive results, analyzed by non-statistical methods, and the problem in the study required a thorough, extensive, and in-depth exploration. The results of the analysis showed that textually, the textbooks used were textbooks that were prepared based on standards of government regulations regarding textbooks.